2020
DOI: 10.1289/ehp5862
|View full text |Cite
|
Sign up to set email alerts
|

Role of TET Dioxygenases and DNA Hydroxymethylation in Bisphenols-Stimulated Proliferation of Breast Cancer Cells

Abstract: BACKGROUND: Bisphenol A (BPA), a ubiquitous environmental endocrine disruptor targeting estrogen receptors (ERs), has been implicated in the promotion of breast cancer. Perinatal exposure of BPA could induce longitudinal alteration of DNA hydroxymethylation in imprinted loci of mouse blood cells. To date, no data has been reported on the effects of BPA on DNA hydroxymethylation in breast cells. Therefore, we asked whether BPA can induce DNA hydroxymethylation change in human breast cells. Given that dysregulat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
24
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(27 citation statements)
references
References 73 publications
3
24
0
Order By: Relevance
“…Higher proliferation in ER-positive breast cancer cells is noted following treatment with BPA or its substitute, BPS, accompanied by an ERĪ±-dependent decrease in genomic TET-catalyzed DNA hydroxymethylation. These findings highlight the E2-like activity of BPA/BPS and the epigenetic impact on breast tumorigenesis (97). The exposure of MCF-7 cells to BPS induces DNA methylation of transposons.…”
Section: Bpa Analogsmentioning
confidence: 63%
“…Higher proliferation in ER-positive breast cancer cells is noted following treatment with BPA or its substitute, BPS, accompanied by an ERĪ±-dependent decrease in genomic TET-catalyzed DNA hydroxymethylation. These findings highlight the E2-like activity of BPA/BPS and the epigenetic impact on breast tumorigenesis (97). The exposure of MCF-7 cells to BPS induces DNA methylation of transposons.…”
Section: Bpa Analogsmentioning
confidence: 63%
“…The study by Dolinoy et al [58] using this model found that the methyl-donors genistein and folate could reverse the hypomethylating effects of BPA, which caused a yellow coat color in viable yellow agouti mouse offspring. A recent work by Li et al [59] found that BPA-induced proliferation of MCF-7 cells was found to be mediated through suppression of DNA hydroxymethylation. Specifically, Ten-eleven translocation (TET)2 plays a direct role in DNA hydroxymethylation in response to BPA through interaction with ERĪ± [59].…”
Section: Epigenetic Mechanisms Of Bpa Actionmentioning
confidence: 99%
“…A recent work by Li et al [ 59 ] found that BPA-induced proliferation of MCF-7 cells was found to be mediated through suppression of DNA hydroxymethylation. Specifically, Ten-eleven translocation (TET)2 plays a direct role in DNA hydroxymethylation in response to BPA through interaction with ERĪ± [ 59 ]. This novel pathway suggests a potential mechanism through which epigenetics play a role in breast cancer development in response to BPA exposure.…”
Section: Molecular Mechanisms Of Bpa In Breast Cancermentioning
confidence: 99%
“…Cancer cell proliferation has been reported to be mediated by DNA methylation induced by BPA exposure. Recently, Li et al (2020) revealed the pivotal role of TET dioxygenases and DNA hydroxymethylation in the bisphenol-stimulated proliferation of breast cancer cells. They found that BPA or its replacement BPS increased the promoter methylation of TET2, leading to an inhibition of TET2 expression and DNA hydroxymethylation.…”
Section: Bpa and Dna Methylationmentioning
confidence: 99%